Late Holocene cultural dynamics and trans-Saharan connections in Southeastern Mauritani: a remote sensing approach - Linares Matás, GJ (2023)
This doctoral thesis investigates the prehistoric and medieval archaeological record of southeastern Mauritania (c. 2,000 BC to AD 1,100). The highlands of southeastern Mauritania present an extraordinary archaeological record for documenting the emergence, consolidation, and reorganisation of cultural dynamics. A remote sensing approach represents the most viable research methodology, politically and logistically, for this study. My work integrates quantitative methods and transdisciplinary theoretical developments to characterize and assess diachronic cultural trends in terms of regional settlement dynamics, the nature of funerary landscapes, and supra-regional connectivity. The results include the identification and spatial distribution mapping of >9,000 funerary tumuli and 1,140 settlements belonging to the Tichitt Tradition, many of which were previously unpublished or undocumented.